Prevalence of chronic kidney disease of non-traditional causes in patients on hemodialysis in southwest Guatemala - Timothy S. Laux; Joaquin Barnoya; Ever Cipriano; Erick Herrera; Noemi Lopez; Vicente Sanchez Polo; Marcos Rothstein
ABSTRACT Objective To document the prevalence of patients on hemodialysis in southwestern Guatemala who have chronic kidney disease (CKD) of non-traditional causes (CKDnt). Methods This cross-sectional descriptive study interviewed patients on hemodialysis at the Instituto Guatemalteco de Seguridad Social on their health and occupational history. Laboratory serum, urine and vital sign data at the initiation of hemodialysis were obtained from chart reviews. Patients were classified according to whether they had hypertension or obesity or neither. The proportion of patients with and without these traditional CKD risk factors was recorded and the association between demographic and occupational factors and a lack of traditional CKD risk factors analyzed using multivariate logistic regression. Results Of 242 total patients (including 171 non-diabetics) enrolled in hemodialysis in southwestern Guatemala, 45 (18.6% of total patients and 26.3% of non-diabetics) lacked traditional CKD risk factors. While agricultural work history was common, only travel time greater than 30 minutes and age less than 50 years old were significantly associated with CKD in the absence of traditional risk factors. Individuals without such risk factors lived throughout southwestern Guatemala's five departments. Conclusions The prevalence of CKDnT appears to be much lower in this sample of patients receiving hemodialysis in Southwestern Guatemala than in hospitalized patients in El Salvador. It has yet to be determined whether the prevalence is higher in the general population and in patients on peritoneal dialysis.